Balzac: An Artist and an Entrepreneur (Asian Journal of Social Science Studies, 2019)
Balzac has been widely regarded as one of the greatest storytellers of humanity; his ability to describe an entire universe of characters makes his work a real living system, truly devoted to an ambitious project. At the same time his sparkling and puzzled existence is itself a novel. As such, analyzing some key moments in Balzac's life, from a specific financial standpoint and business perspective, allows us to better understand the genesis of his work: and vice versa. In effect, the main research question of this paper is to identify some key moments in Balzac's life that have affected him from a financial perspective and that have drawn him to a mature and profound knowledge of the social and economic mechanisms, essential for writing his great masterpieces. At the same time, and on the contrary direction, attention will be devoted to some of his novels that have a clear economic and financial plot: as above, they certainly have emerged from the knowledge of the social life in France in the nineteenth century via his daily vicissitudes.